Sedimentology of Archean Turbidites at Yellowknife, Northwest Territories - Henderson, John B. (Canadian Journal of Earth Sciences, 1972)
The Burwash Formation is a major formation of the Archean Yellowknife Supergroup at Yellowknife. It consists of about 15 000 ft (4572 m) of interbedded graywackes and mudstones and shows many of the features characteristic of turbidites. Analysis of the internal sedimentary structures and paleocurrent data on the sediments indicate that the sediments were derived from the west, possibly from an area now occupied by an extensive granitic terrain, and accumulated in depositional fan valleys on a submarine fan complex near the margin of a large Archean sedimentary basin that lies to the east of Yellowknife. The high proportion of volcanic rock fragments, particularly silicic–volcanic lithic clasts, along with abundant quartz and feldspar and the minor but ubiquitous granitic rock fragments in the graywackes, indicates a mixed silicic–volcanic and granitic provenance. The modal and chemical composition, and volumetric abundance, of these sediments denotes the presence, and considerable extent, of sialic crust prior to the deposition of the Burwash Formation.